Directory of Australian Multicultural Films and Videos : a resource guide for community groups, teachers, film-makers, researchers, librarians - Best, Alleyn (Melbourne : Australian Institute of Multicultural Affairs, 1985)
This directory is a guide to films and videos dealing with migration, migrant issues, and multiculturalism in Australia. Current and archival films are listed and most of the research sources used to obtain the listings are included in the directory. Section 1 lists documentaries and feature films; each citation includes title, production company (or director), year of production, format details, a brief description of the film, film-lending collections that have the film available for hire or viewing, and library catalog numbers, where applicable, that are used when ordering the film. The listing is prepared alphabetically and each item is numbered for ease of reference when using the subject index. Sections 2 and 3 list newsreel and television items and other archival film material, using an availability code where applicable. Section 4 contains the complete address for each lending organization mentioned in the directory. There are two indexes to the films, one by subject and the other by title and number. The directory lists only such films as deal with social and/or cultural issues relating to migration and migrant issues. (CG)
Includes bibliographical references and index
Community.
Researchers.
Practitioners.
Microfiche.
Keywords: Immigrants -- Australia - film catalogs - Union list; Multiculturalism -- Australia - film catalogs